Koptihub: A UI/UX Design for Transparent Procurement using a User-Centered Design Approach - Satyaninggrat, Luh Made Wisnu; Hamijaya, Prasis Damai Nursyam (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The traditional procurement process faces significant inefficiencies and transparency issues, including low efficiency, limited oversight, and challenges in securing competitive supplier engagement and a stable soybean supply. To address these issues, this study aims to design and evaluate Koptihub, a prototype that enhances communication with importers, improves transparency in price comparisons, streamlines stock management, and optimizes transaction monitoring and decision-making. The research employs the User-Centered Design (UCD) approach, integrating User Experience (UX) principles and cooperative member feedback to develop a prototype using Figma. The system's effectiveness, clarity, and user-friendliness were assessed through usability testing with 15 participants using the System Usability Scale (SUS). The prototype incorporates key features such as notifications, incoming offers, price offer status, orders in process, order delivery status, payments, refunds, and a chat function for cooperative-importer communication. The usability test results yielded an SUS score of 82.17, classified as an A grade, indicating high usability and strong user acceptance. These findings confirm that the system effectively supports efficient price selection, order tracking, and enhanced transparency in procurement. This study introduces an innovative e-procurement solution tailored for cooperatives, demonstrating the potential of digital procurement platforms to transform cooperative procurement processes. The proposed model serves as a practical framework that can be adapted by similar cooperatives to improve procurement efficiency and supplier engagement.